2019
DOI: 10.1002/ppul.24421
|View full text |Cite
|
Sign up to set email alerts
|

Solar radiation, air pollution, and bronchiolitis hospitalizations in Chile: An ecological study

Abstract: Objective To evaluate trends and geographic distribution of infant bronchiolitis hospitalizations in Chile, a country with large variation in solar radiation (SR) and high rates of urban air pollution. Methods We performed a nationwide ecological study of bronchiolitis hospitalizations from 2001 to 2014. We investigated the associations of regional SR (a proxy of vitamin D status) and regional fine particulate matter (PM2.5) air pollution with bronchiolitis hospitalizations. We also evaluated the role of socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
0
0
1
Order By: Relevance
“…Furthermore, the prospective cohort study conducted by Milani et al, 31 showed a direct association between PM 2.5 exposure in the few days before and the 2-3 weeks before and the severity of bronchiolitis, and the study conducted by Gallo et al 25 showed a significant association between PM 2.5 exposure in the days before the bronchiolitis and an increased risk of presentation to the PED. Terrazas et al 33 reported a significant correlation between PM 2.5 levels and hospitalizations for bronchiolitis for a longer exposure than in our study (i.e., 1 year). Moreover, the studies by Nenna et al 10 and Vandini et al 9 found correlations between RSV bronchiolitis and PM 2.5 , but this pollutant did not prove to be a proper predictor for hospitalization by applying the regression model.…”
Section: Discussioncontrasting
confidence: 52%
“…Furthermore, the prospective cohort study conducted by Milani et al, 31 showed a direct association between PM 2.5 exposure in the few days before and the 2-3 weeks before and the severity of bronchiolitis, and the study conducted by Gallo et al 25 showed a significant association between PM 2.5 exposure in the days before the bronchiolitis and an increased risk of presentation to the PED. Terrazas et al 33 reported a significant correlation between PM 2.5 levels and hospitalizations for bronchiolitis for a longer exposure than in our study (i.e., 1 year). Moreover, the studies by Nenna et al 10 and Vandini et al 9 found correlations between RSV bronchiolitis and PM 2.5 , but this pollutant did not prove to be a proper predictor for hospitalization by applying the regression model.…”
Section: Discussioncontrasting
confidence: 52%